AN ASSESSMENT OF THE USE OF SOCIAL MEDIA FOR CUSTOMER ENGAGEMENT BY LARGE BANKS IN KENYA - Namiinda, Barbara M. (IJRDO - Journal of Business Management, 2017)
The purpose of this paper is to assess the use of social media by the large banks in Kenya in enhancing customer engagement. Social media provides an opportunity for brands to build on their customer relationships and improve on their customer‟s satisfaction. This study specifically looks at the large banks in Kenya .A bank with a weighted composite index of 5 percent and above is classified as a large by the Central Bank of Kenya.This study will use content analysis.This is a set of procedures for the systematic replicable analysis of text by classifying parts of a text through the application of a structured, systematic coding scheme from which conclusions can be drawn about the message content (Rose, Spins and Canhoto,2015). Rose et al(2015) observe that the rise of the internet creates opportunities for using content analysis to analyze online communication.This research paper found out that the big banks in Kenya have not harnessed the power of social media in their engagement with customers.Despite their being various social media tools,the six banks classified as big by the Central Bank of Kenya only use social networking sites like Facebook and twitter and content communities like you tube. The use of these tools is also wanting as the customer engagement by some of the big banks is minimal with an average of seven posts per month or none at all.It is also noted that some banks do not respond to all customer enquiries on their social media pages. However some banks like Equity Bank are very active on social media and are even able to respond to customer queries and complaints on social media. This research paper only looked at the large banks in Kenya.The Kenyan banking industry consists of 43 banks, six classified as big. This therefore means that the results may not be generalized to the whole banking industry.